FORMATION OF TEACHER’ READINESS FOR WORK WITH SOMATICALLY WEAKENED PUPILS IN THE PROFESSIONAL DEVELOPMENT SYSTEM - Сємічєнко, В. А. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2017)
The article deals with the psychological problems with children who are often ill. Teachers turn out not to often realize it, and therefore do not provide the necessary help. The concept of teachers’ readiness for work with somatically weakened children is introduced, the corresponding theoretical model is proposed. Based on the results of empirical studies data on the formation of individual components of readiness is obtained. The program for increasing the level of primary school teachers’ readiness to interact with this category of pupils is offered, and the effectiveness of its implementation in the teachers professional development system is proved